Effects of Training and Compensation Practices on Employee Performance in Public Universities in Kenya - Kinyamu, Sylvia Igoki; Nkaabu, Clement; Moguche, Abel (International Journal of Professional Practice, 2021)
Effective human resource management practices are associated with increased performance of employees. This study aimed to determine the relationship between training and compensation practices on employee performance in public universities in Kenya. The objectives of the study were to determine the effect of training on employee performance in public universities in Kenya, and to establish the effect of compensation practices on employee performance in public universities in Kenya. A survey approach was used. The study targeted all 201 Office Administration Officers working in six public universities in Mt. Kenya Region. Mt. Kenya region comprises the counties of Nyeri, Kirinyaga, Nyandarua, Tharaka Nithi, Embu and Meru. A questionnaire consisting of demographic questions and a 5-point Likert Scale was used to collect data. Qualtrics survey was utilized to administer the questionnaire. Out of 201 sets of questionnaires distributed, 176 responses were generated, representing a response rate of 88%. Descriptive statistics in form of tables, frequencies and percentages were used to present the analysed data. Cronbachs alpha was used to assess the reliability of instruments, while content validity was assessed through reviews of items. Data was tested to ensure that it did not violate regression assumptions. The study revealed that workers’ performance was significantly influenced by training practice (p<0.05), while the effect of compensation practice on workers’ performance was not significant (p>0.05). The study, therefore, concluded that training and compensation practices were associated with increased performance of the workers in public universities in Kenya. The results imply that the management of public universities needs to focus on improvement of each of the aforementioned practices through the establishment of relevant policies. There is need for further research on other human resources practices, and preferably be undertaken in a different geographical and organisational setting